Bioenergetic Constraints on Microbial Hydrogen Utilization in Precambrian Deep Crustal Fracture Fluids. Issue 2 (7th February 2018) - Telling, Jon; Voglesonger, Ken; Sutcliffe, Chelsea N.; Lacrampe-Couloume, Georges; Edwards, Elizabeth; Sherwood Lollar, Barbara
ABSTRACT: Precambrian Shield rocks host the oldest fracture fluids on Earth, with residence times up to a billion years or more. Water–rock reactions in these fracture systems over geological time have produced highly saline fluids, which can contain millimolar concentrations of H2 . Mixing of these ancient Precambrian fluids with meteoric or palaeo-meteoric water can occur through tectonic fracturing, providing microbial inocula and redox couples to fuel blooms of subsurface growth. Here, we present geochemical and microbiological data from a series of borehole fluids of varying ionic strength (0.6–6.4 M) from the Thompson Mine (Manitoba) within the Canadian Precambrian Shield. Thermodynamic calculations demonstrate sufficient energy for H2 -based catabolic reactions across the entire range of ionic strengths during mixing of high ionic strength fracture fluids with meteoric water, although microbial H2 consumption and cultivable H2 -utilizing microbes were only detected in fluids of ≤1.9 M ionic strength. This pattern of microbial H2 utilization can be explained by the higher potential bioenergetic cost of organic osmolyte synthesis at increasing ionic strengths. We propose that further research into the bioenergetics of osmolyte regulation in halophiles is warranted to better constrain the habitability zones of hydrogenotrophic ecosystems in both terrestrial subsurface, including potential future radioactive waste disposal sites, and other planetary body crustal environments, including Mars.